The position of women in Islam : a progressive view - Ali, Syed Mohammed (State University of New York Press, 2004)
"Challenging the conservative framers of Islamic law who accorded a lesser status to women, Mohammad Ali Syed argues that the Quran and the Hadith - the two primary sources of Islamic law - actually place Muslim women on the same level as Muslim men. Syed provides an overview of both sources and explores their respective roles in Islamic law, emphasizing the Quran's role as the supreme authority and questioning the authenticity of some of the alleged sayings of the Prophet Muhammad (pbuh). From these texts, he elaborates women's rights in a variety of areas, including treatment by God; marriage, divorce, financial provisions, and custody of children; coming out of seclusion (purdah), and taking part in social, economic, legal, and political activities. Rather than presenting what is practiced today, the book covers the theoretical position of Muslim women as sanctioned by the Quran and the authentic Hadith and offers a glimpse of the exalted position of honor and dignity enjoyed by Muslim women in the early days of Islam." "This well-researched book is made more distinctive by the author's personal experience. Raised in Bengal, India, Syed was inspired by his family, who valved men and women equally. As he grew up, Syed realized that most Muslim women lived very differently than the women of his family. According to the author, his family was egalitarian because his father and male relatives were not only devout Muslims but also very knowledgeable about Islam. This book is a culmination of his lifelong concern for women's right under Islam."--Jacket.